Study of Indonesian Rhododendron: Classification, Conservation, and Pharmacology Activity - Birhi, Damiana Nofita; Meike Tiya Kusuma; Antonia Fransiska Laka (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2025)
Rhododendrons are representatives of ornamental plants with a wide range of pharmacological activities. Indonesia is the second richest country in Rhododendron plants with 233 species. Unfortunately, more than 85 species are severely lacking in data, 21 species are vulnerable, and more than 30 others are endangered or even no longer found. The purpose of this study is to review the species that have been found in Indonesia, and find the factors that affect conservation efforts to prevent the extinction of this plant. The results of the study succeeded in recording 221 species that had been found in Indonesia with 4 of them not having sufficient data so that named Rhododendron sp1, R. sp2, R. sp3 and R. sp4 by local residents. Four species were confirmed to be extinct, and most of the ex-situ conservation efforts unsuccessful. The results of this study show that there is need for cooperation between the government and residents around the Rhododendron growing location in an effort to preserve this plant. Researchers are also expected to pay more attention to this plant considering it has bioactive compounds with very high pharmacological properties.